2015
DOI: 10.1016/j.ijhydene.2015.07.135
|View full text |Cite
|
Sign up to set email alerts
|

Platinum–tin/carbon catalysts for ethanol oxidation: Influence of Sn content on the electroactivity and structural characteristics

Abstract: A series of Pt x -Sn y /C catalysts with different atomic ratios (x:y = 1:1, 2:1, 3:1) and diameters (~4 nm) were easily synthesized by a deposition process using formic acid as the reducing agent.Catalyst structure and chemical composition were investigated by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray powder diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). XRD and SEM showed that the geometric environment was changed with Sn addition to the fcc Pt crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…It should be pointed that the O1s spectra for the Pt/CNDs electrocatalyst (Figure b) shows six peaks, the seventh peak observed for this Pt‐Sn/CNDs electrocatalyst was due to the presence of tin bonded through the oxygen atoms. When comparing the Pt/CNDs and Pt‐Sn/CNDs electrocatalysts, it is noted that the binding energies of the O1s spectrum for the Pt‐Sn/CNDs electrocatalyst shift to lower values to the due to the contribution of Sn which is believed to be bonded to the carbon nanodots through C=O functional group to form Sn‐O species . The deconvoluted C1s spectrum (Figure c) for the Pt‐Sn/CNDs electrocatalyst shows six peaks at 286.15 eV, 284.00 eV, 283.08 eV, 282.54 eV, 282.01 eV and 281.40 eV which were ascribed to the presence of O=C−C, C−C, Pt, C=C and Sn as labelled in the spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be pointed that the O1s spectra for the Pt/CNDs electrocatalyst (Figure b) shows six peaks, the seventh peak observed for this Pt‐Sn/CNDs electrocatalyst was due to the presence of tin bonded through the oxygen atoms. When comparing the Pt/CNDs and Pt‐Sn/CNDs electrocatalysts, it is noted that the binding energies of the O1s spectrum for the Pt‐Sn/CNDs electrocatalyst shift to lower values to the due to the contribution of Sn which is believed to be bonded to the carbon nanodots through C=O functional group to form Sn‐O species . The deconvoluted C1s spectrum (Figure c) for the Pt‐Sn/CNDs electrocatalyst shows six peaks at 286.15 eV, 284.00 eV, 283.08 eV, 282.54 eV, 282.01 eV and 281.40 eV which were ascribed to the presence of O=C−C, C−C, Pt, C=C and Sn as labelled in the spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The improved activity of the Pt‐Sn/C electrocatalysts for ethanol oxidation is brought by Sn atoms which serve two functions; (i) Sn provides surface oxygen‐containing species which react with the CO‐like intermediates produced during the oxidation of ethanol and also (ii) modifies the platinum geometric structure resulting in improved activity. It has been observed that Pt‐Sn electrocatalysts give low onset potentials and high current densities during ethanol oxidation in acidic conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the petroleum industry is leading the introduction of nanoparticles as supports for catalysts in several reactions. It has been reported the potential of activated carbon and carbon nanotubes (CNTs) as support for ethanol oxidation [4], aluminosilicates, cordierites [5], zeolites [6], other feldspars, kaolinite derivate such sespiolites [7], HNTs, etc., which allow the conversion of crude oil in a wide range of products.…”
Section: Introductionmentioning
confidence: 99%
“…The Pt-Sn/C electrocatalyst yielded current values higher than those of Pt-Ru/C for both ethanol and methanol oxidation. The superior activity of the Pt-Sn/C nanocatalyst is brought by the "bifunctional" mechanism where Sn provides oxygen-containing species to react with the CO poisoning intermediates on the platinum sites [74][75][76][77][78].…”
Section: Platinum-tin (Pt-sn) Electrocatalystmentioning
confidence: 99%